Leadership Development as Organisational Rehabilitation: Shaping Middle managers as Double Agents - Roddy Walker (Copenhagen Business School (CBS), 2018)
This dissertation contributes to existing research concerning the organisational influence of leadership development, by offering a detailed qualitative study of a diploma programme in leadership provided for middle managers within the municipality of Copenhagen. The social practice theory of Theodore Schatzki offers a conceptualisation of educational and institutional settings as representing interconnected bundles of social practices, allowing consideration of the movement of entities within and between them and the implications this has for the practices taking place. This offers a vocabulary for understanding and analysing the complexity of social practices. In order to gain a richer understanding of the interactions and learning of the people undertaking these practices, a dialogue between social practice theory and social learning theories is facilitated. This offers the opportunity for a bifocal perspective, to be trained on practices and the people populating them, where the shaping of the professional identity of middle managers can be explored.
hdl:10398/9675
Keywords: 650